2013
DOI: 10.7314/apjcp.2013.14.11.6997
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal, Liver and Biliary Tract Pathology: A Histopathological and Epidemiological Perspective from Pakistan with a Review of the Literature

Abstract: Aim: To present an epidemiological and histological perspective of diseases of the gastrointestinal tract (including liver and biliary tract) at the Section of Histopathology, Department of Pathology, AKUH, Karachi, Pakistan. Materials and Methods: All consecutive endoscopic biopsies and resections between October 1 and December 31, 2012 were included. Results: A total of 2,323 cases were included. Carcinoma was overwhelmingly the commonest diagnosis on esophageal biopsies (69.1%); chronic helicobacter gastrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In 2013, we published an epidemiological and histological perspective of diseases of the gastrointestinal tract in Pakistan (Ahmad et al, 2013). In the current article, an epidemiological, histological and risk stratification perspective of GIST is presented.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, we published an epidemiological and histological perspective of diseases of the gastrointestinal tract in Pakistan (Ahmad et al, 2013). In the current article, an epidemiological, histological and risk stratification perspective of GIST is presented.…”
Section: Discussionmentioning
confidence: 99%
“…At present, effective treatment for HCC is still liver resection (including liver resection and liver transplantation, and local ablation) (Abdelgawad et al, 2013;Ahmad et al, 2013;Banjerdpongchai et al, 2013;Berk et al, 2013;Chittmittrapap et al, 2013;Gupta et al, 2013;Hao et al, 2013;Norsa'adah B et al, 2013;Zhu et al, 2013;Zhang et al, 2013;Zekri Ael-R et al, 2013). For patients with early disease, liver resection or liver transplantation could achieve a 5-year survival rate of 60-80%.…”
Section: Discussionmentioning
confidence: 99%
“…From previous reports on HCC from China or other countries, it is suggested that radical resection e.g. surgery, radio frequency or liver transplantation is still the most effective option for HCC treatment (Ye at al., 2009;Abdelgawad et al, 2013;Ahmad et al, 2013;Banjerdpongchai et al, 2013;Berk et al, 2013;Chittmittrapap et al, 2013;Gupta et al, 2013;Hao et al, 2013;Norsa'adah et al, 2013;Zekri Ael-R et al, 2013;Zhang et al, 2013;Zhu et al, 2013). However the invasiveness HCC is strong, and HCC is easy to relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is a common disease in Asian Pacific area, and most medical resources are specially focused on the diagnosis and treatment of this disease (Ahmad et al, 2013;Atrkar-Roushan et al, 2013;Ma et al, 2013;Song et al, 2013;Suh et al, 2013;Tuncel et al, 2013;Zare et al, 2013;Zhang et al, 2013;Zhu et al, 2013). Combined chemotherapy was reported to be superior to the best supportive care in the man¬agement of MGC (Pyrhonen et al, 1995;Jo et al, 2007;Chen et al, 2013;Usakova et al, 2013).…”
Section: Discussionmentioning
confidence: 99%